The Perceived Administrative Pattern and its Relationship with the Career Efficiency among Secondary Schools' Counselors in Jordan - Faraj Al-Sakarneh; Shatha Al Ajeeliy (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
The present study aimed to identify the perceived administrative style and its relationship to the functional competence of educational counselors in secondary schools in Jordan. The study sample consisted of (200) schools' counselors working in public secondary schools in Amman. To achieve the goal of the study, the descriptive and correlative method were used and the administrative pattern and functional efficiency scales were applied on the members of the study sample after verifying their validity and reliability. The results indicated that the democratic consultative style came at a medium level, and that the functional competence of counselors came at medium level. The study showed that there was a positive relationship between the perceived administrative style and the functional competence of the educational counselors in the public secondary schools in Jordan. The results indicated that there are statistically significant differences according to the gender variable for the democratic consultative style in favor of males, and the presence of statistically significant differences according to the variable of experience for the goodness authoritarian style in favor of experience more than (10) years. The study recommended that the directorates of education should pay attention to the administrative Pattern of managers because of their impact on the career efficiency of educational counselors.